Clothes Deferred Maketh the Heart Sick cartoon, 1942 (1942)
1942 1939-1945 "Clothes Deferred Maketh the Heart Sick cartoon, 1942" [HFR0082], 1942 After the introduction of clothes rationing, additional coupons were issued to industrial workers whose clothes were lost or damaged during war work or while undertaking fire prevention duties. . This cartoon by Batt appeared in the National Union of Railwaymen Railway Review, 16 October, 1942.